Dynamic cyclic fatigue resistance of NiTi instruments in a double-curved stainless steel canal with variable distances of displacement - Pham, Van-Khoa (Frontiers in Materials, 2023)
The present study aimed to measure the number of cycles to fracture (NCF) of different instruments using pecking motion at constant and varying distances of movement at body temperature. This study included 20 files from each brand: ProTaper Universal F2, ProTaper Next X2, and WaveOne Gold Primary (Dentsply Sirona, Maillefer, Ballaigues, Switzerland). Instruments from each brand were divided into two groups (ten files for each group) that experienced constant or variable distances in a stainless-steel artificial double-curved canal in a platform that ensured that the instrument rotated at a stable temperature with a minimum fluctuation of the environment. While running, the platform was programmatically controlled to move at any desired distance of instrument displacement to simulate the clinical pecking motion at variable distances. The files were rotated using proprietary programs. The times to fracture were recorded and then transformed into the number of cycles to fracture (NCF). Data were analyzed using Minitab with proper tests. All fragments were observed under a scanning electron microscope to capture and describe the characteristics of the fracture surface. The WaveOne Gold had the highest NCF, while the ProTaper Universal had the lowest NCF. The manufacturer brands and the modes of displacement of the experimental instrument showed interactive effects. The fracture surface revealed no striation. A new design, material, mode of rotation, and different distances of movement have certain effects on the cyclic fatigue resistance of the instrument.